Five new Myxomycetes (Myxogastria) records from Turkey - Baba Hayri̇ (Phytotaxa, 2021)
Myxomycetes samples were obtained from Adana and Hatay provinces of Turkey. As a result of field and laboratory studies five myxomycetes species are reported as new records. Three of the new records (Arcyria cerradensis, Craterium aureonucleatum and Diderma spumarioides) were found as natural sporophore in the area. The other two species (Cribraria spinispora and Perichaena quadrata) were grown in the laboratory by moist chamber culture method. Short descriptions, habitats, localities, collection dates, fungarium numbers and images of the taxa are given. This work has contributed to Myxobiota of Turkey.